Diari cinta fathi - Nazir, Faridah (Wacana MBM, 2020)
This novel tells the story of the turmoil of life that Sharifah Fathidatul Akma went through in navigating life as a wife. Sharifah Fathidatul Akma is a girl of Arab descent. His father still adhered to the tradition of not allowing his children to marry other descendants. But in silence, Sharifah Fathidatul Akma objected to her father's decision and was more open in finding a mate. This novel begins with the experience of Sharifah Fathidatul Akma while continuing her studies at Universiti Kebangsaan Malaysia. Although it had been warned by his father not to intimate relationships, especially with guys Malay, a mate prevail. Sharifah Fathidatul Akma met Fadzli.